The relationships between the bubble–particle attachment time, collector dosage and the mineralogy of a copper sulfide ore - Albijanic, Boris; Bradshaw, D.; Nguyen, A. (Elsevier, 2012)
Flotation occurs as a result of bubble–particle attachment. This is controlled by the particle surface properties which are created by surface liberation of valuable minerals and collector adsorption within the chemical environment. This paper examines the contribution of both collector dosage and liberation of valuable minerals to bubble–particle attachment time measurements. In order to evaluate particles of different liberation, the bubble–particle attachment time measurements were conducted with a sized fraction of concentrates and tails obtained by flotation of a copper sulfide ore (Northparkes Mine, Australia) in a mechanically agitated batch flotation cell. Quantitative mineral liberation analysis was performed to analyze all concentrates and tails. The results indicated that for particles with high Cu grade, a small increase of collector dosage resulted in a dramatic reduction of attachment time with no further increase on subsequent addition of collector. However, for particles with moderate Cu grade, the effect of collector addition on attachment time was reduced much less because valuable minerals were mainly moderately and poorly liberated. For particles with low Cu grade, collector addition made no difference. All these results confirmed that there is a highly non-linear correlation between mineral liberation, Cu grade, collector dosage and attachment time.